2017
DOI: 10.1038/s41598-017-04590-z
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfide Na2S4 regulates the activation of PTEN/Akt/CREB signaling and cytotoxicity mediated by 1,4-naphthoquinone through formation of sulfur adducts

Abstract: Electrophiles can activate redox signal transduction pathways, through actions of effector molecules (e.g., kinases and transcription factors) and sensor proteins with low pKa thiols that are covalently modified. In this study, we investigated whether 1,4-naphthoquinone (1,4-NQ) could affect the phosphatase and tensin homolog (PTEN)–Akt signaling pathway and persulfides/polysulfides could modulate this adaptive response. Simultaneous exposure of primary mouse hepatocytes to Na2S4 and 1,4-NQ markedly decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
4
23
1
Order By: Relevance
“…However, a higher dose of xenobiotic electrophiles causes nonspecific protein modification, disrupting these signals, leading to cell death. Our previous studies confirmed such a dose-dependent transition, focusing on some sensor proteins that mediate cellular redox signaling pathways during exposure to xenobiotic electrophiles; phosphatase and tensin homologue (PTEN) modification by MeHg [11] and 1,4-NQ [75] as well as heat shock protein 90 (HSP90) by 1,4-NQ [12] and cadmium [77]. The fact that these xenobiotic electrophile-mediated redox signaling pathways and cellular toxicity are negatively regulated by RSS through the formation of their sulfur adducts, indicate that RSS act as the initial defense system for xenobiotic electrophile exposure [12,75,77] (Figure 3).…”
Section: Protective Function Of Rss Against Electrophilic Stresssupporting
confidence: 60%
See 3 more Smart Citations
“…However, a higher dose of xenobiotic electrophiles causes nonspecific protein modification, disrupting these signals, leading to cell death. Our previous studies confirmed such a dose-dependent transition, focusing on some sensor proteins that mediate cellular redox signaling pathways during exposure to xenobiotic electrophiles; phosphatase and tensin homologue (PTEN) modification by MeHg [11] and 1,4-NQ [75] as well as heat shock protein 90 (HSP90) by 1,4-NQ [12] and cadmium [77]. The fact that these xenobiotic electrophile-mediated redox signaling pathways and cellular toxicity are negatively regulated by RSS through the formation of their sulfur adducts, indicate that RSS act as the initial defense system for xenobiotic electrophile exposure [12,75,77] (Figure 3).…”
Section: Protective Function Of Rss Against Electrophilic Stresssupporting
confidence: 60%
“…This indicates that RSS are involved in the repression of electrophile-mediated toxicity by the formation of inactive metabolites of electrophiles. Consistent with this notion, the toxicity of MeHg, Cd and 1,4-NQ was effectively blocked by treatment with the model polysulfide Na 2 S 4 [75,77,80].…”
Section: Protective Function Of Rss Against Electrophilic Stresssupporting
confidence: 54%
See 2 more Smart Citations
“…In particular, mesoporous metal oxides prepared by a modified EISA method were easily obtained, where some cationic active species can be uniformly incorporated into the framework to form the specific catalysts . The product 1,4‐naphthoquinone, which was widely used in various fields such as medicine, biology, and perfumery, can be obtained by selective oxidation of naphthalene with hydrogen peroxide over various mesoporous metal oxides. However, since liquid‐phase oxidation of naphthalene was a continuous reaction, 1,4‐naphthoquinone as an intermediate product was easily further oxidized, where some chemicals with low values would be formed .…”
Section: Introductionmentioning
confidence: 99%